IMPLEMENTASI TEKNOLOGI VIRTUAL REALITY SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN PEMAHAMAN SISTEM TATA SURYA PADA SISWA SEKOLAH DASAR - Suhadi Parman; Ine Rachmawati; Yuni Awalaturrohmah Solihah; Iqbal Mubarok; Shafa Salsabila (Jurnal Digit : Digital of Information Technology, 2026)
Virtual Reality (VR) is a technology that allows users to interact within a simulated digital environment that closely resembles the real world. This technology holds great potential as an interactive and engaging learning medium, especially for topics that are difficult to comprehend through conventional methods. In this research, a VR application called VIRTYA (Virtual Reality Tata Surya) was developed to help elementary school students understand the concept of the Solar System.The Solar System is often challenging for students to grasp due to its abstract nature, which is typically presented only through illustrations and videos. With the VIRTYA application, students can virtually explore the Solar System, view the planets in realistic 3D representations, and interact with celestial objects. The application was built using Unity 3D and Google VR SDK, and implemented on Android devices with the aid of Google Cardboard.The development of this application followed the System Development Life Cycle (SDLC), which was adapted to the specific needs and stages of the project. This application aims to enhance students' understanding of the Solar System by offering a more interactive and visually engaging approach compared to traditional teaching methods.Kata kunci: Virtual Reality, Solar System, Unity, Google VR SDK, Interactive Learning